At the limit of the obscene : German realism and the disgrace of matter - Weitzman, Erica (Northwestern University Press, 2021)
"At the Limit of the Obscene: German Realism and the Disgrace of Matter examines the fear of materiality in German-language realist and postrealist literature"--